Metall-ooxidoreductase Enzymes: Possible Biomarkers of Gynecological Tumors - Lidia González Méndez; Ahmed Amaury Ruíz Moré; Ana Victoria de la Torre Santos; Elena Carvajal Ciomina; Isabel de Armas Fernández; Arturo Águila Águila (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
The incidence of gynecological epithelial tumors and their diagnosis in advanced stages cause physical damage, impact on reproductive health and produce psychological effects in women. Reducing the time of its detection constitutes a great challenge for public health. The knowledge and validation of various enzymatic study methods, applied to tumor pathology, will allow the integration of each result into the network of reactions, molecular and cellular recognition mechanisms, as well as signaling pathways, useful for understanding the disease and its diagnostic and therapeutic mechanisms. The determination of the activity of metallo-oxidoreductases enzymes in serum is an attempt to implement liquid biomarkers for the early diagnosis and prognosis of gynecological tumors. The aim of the research is the compilation of updated information about enzyme biomarkers for the prediction, diagnosis and follow-up of gynecological epithelial tumors.